On the history of vectorcardiography: past, present, future - Elena S. Yurasova; Elena V. Blinova; Tamara A. Sakhnova (Терапевтический архив, 2022)
The vector concept in the analysis of the electrical signals of the heart began to be used at the dawn of the development of electrocardiology. For several decades, vectorcardiography has developed in parallel with electrocardiography; reached its peak in the 60s, and after a period of cooling experienced a resurgence since the early 90s, when it became possible to mathematically synthesize vectorcardiograms (VCG) from digital electrocardiograms in 12 leads. VCG reflects the same phenomena as electrocardiography, but allows you to calculate and visualize a number of three-dimensional characteristics of the electrical signals of the heart. The article describes the main milestones in the development of the VCG, the history of international cooperation in this area, the contribution of domestic scientists to this field of science. Modern promising areas of research related to the vector concept of the analysis of the electrical signals of the heart are briefly reflected.